IR spectrometer i-Red 7800 series «SILab» for quality control in pharmaceutical plants - article Editorial (Разработка и регистрация лекарственных средств)
The use of IR spectroscopy in the quality control of medicines is regulated by the State Pharmacopoeia of the Russian Federation, the Pharmacopoeia of the USA and the European Pharmacopoeia. Labconcept Group, a leading supplier and manufacturer of analytical and general laboratory equipment, offers IR spectrometers i-Red 7800 series under its own brand SILab. The IR spectrometers of the i-Red 7800 series are supplied with a wide range of additional accessories allowing to solve any identification and quality assessment tasks pharmaceutical substance, quantitative analysis.